2015
DOI: 10.1016/j.jpain.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned Placebo Analgesia Persists When Subjects Know They Are Receiving a Placebo

Abstract: Belief in the effectiveness of a placebo treatment is widely thought to be critical for placebo analgesia. Many types of placebo responses—even those that depend on conditioning—appear to be mediated by expectations that are strengthened as treatment cues are reinforced with positive outcomes. However, placebo effects may occur even when participants are aware they are receiving placebo. To address the question of whether conditioned placebo analgesia can persist in the absence of expectations, we studied the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 38 publications
5
96
1
2
Order By: Relevance
“…These results are also in line with prior research that showed that placebo conditioned hypoalgesic effects persist after revealing that the cream used to reduce the experimental heat pain was merely Vaseline [10]. Therefore, it appears that informing study participants about the precise nature of the placebo manipulation and its mechanisms yields no negative reactions or negative consequences and actually may favor outcome improvements throughout increasing participant engagement.…”
supporting
confidence: 88%
“…These results are also in line with prior research that showed that placebo conditioned hypoalgesic effects persist after revealing that the cream used to reduce the experimental heat pain was merely Vaseline [10]. Therefore, it appears that informing study participants about the precise nature of the placebo manipulation and its mechanisms yields no negative reactions or negative consequences and actually may favor outcome improvements throughout increasing participant engagement.…”
supporting
confidence: 88%
“…Although a full discussion of ethical aspects is beyond the scope of this article (reviewed elsewhere 174,175 ), it is important to draw attention to emerging evidence from clinical trials in patients with IBS, 83 major depression 176 and migraine 171 that 'openlabel' placebo treatment might be efficacious and is also supported by experimental data. 177,178 Similarly, application of conditioning principles could pave the way to reduce the amount of medication needed 179,180 and/or to reduce adverse events such as conditioned nausea. 142,181 These improvements in care could be achieved with the informed consent of patients and thereby overcome ethics restraints in this field.…”
Section: Discussionmentioning
confidence: 99%
“…That is, even though you know that you are using a placebo, it can still work, at least to a certain degree, and under certain conditions [60]. Maybe here the key thing distinguishing the augmenting of the olfactory element of a dish in the modernist restaurant case and that described in the adulterated whiskey (or should/could that read whisky?)…”
Section: On the Authenticity Of Flavoursmentioning
confidence: 99%